Antibiotic Resistance and Ways to Overcome It. Commentary on the Article of Svetlana V. Ilyina «Irrational Use of Antibiotics in Medicine: Crisis of Antibiotic Resistance and what We Can Do» - Vladimir K. Tatochenko (Педиатрическая фармакология)
.